2022
DOI: 10.1021/acsnano.1c10755
|View full text |Cite
|
Sign up to set email alerts
|

Improving Wastewater Treatment by Triboelectric-Photo/Electric Coupling Effect

Abstract: The ability to meet higher effluent quality requirements and the reduction of energy consumption are the biggest challenges in wastewater treatment worldwide. A large proportion of the energy generated during wastewater treatment processes is neglected and lost in traditional wastewater treatment plants. As a type of energy harvesting system, triboelectric nanogenerators (TENGs) can extensively harvest the microscale energies generated from wastewater treatment procedures and auxiliary devices. This harvested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 273 publications
0
29
0
Order By: Relevance
“…Overall, despite the fact that the state-of-the-art fabric/fiber structured TENG has a few flaws, it considerably advances the development of wearable self-powered sensors and makes it feasible to create green flexible wearable power sources. Furthermore, fabric/fiber structured TENGs are also expected to applied in other fields, such as food detection, wastewater treatment and electro-catalysis [ 78 , 79 , 80 , 81 ]. It is hoped that fabric/fiber structured TENGs would continue to provide scientists with fresh insights and provide further research results.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, despite the fact that the state-of-the-art fabric/fiber structured TENG has a few flaws, it considerably advances the development of wearable self-powered sensors and makes it feasible to create green flexible wearable power sources. Furthermore, fabric/fiber structured TENGs are also expected to applied in other fields, such as food detection, wastewater treatment and electro-catalysis [ 78 , 79 , 80 , 81 ]. It is hoped that fabric/fiber structured TENGs would continue to provide scientists with fresh insights and provide further research results.…”
Section: Discussionmentioning
confidence: 99%
“…Even at low velocity, high shear stress is still present, which is helpful to improve cleaning efficiency. The attractive feature can be attributed to the high slip pressure difference and Bingham characteristics of the thick slurry. , Similarly, Quarini et al also reported that ice slurries demonstrated the ability to remove sand at the bottom of various tubes at relatively low velocity . Moreover, a series of initial in-ground experiments were undertaken to prove that ice pigging is beneficial in cleaning in service mains.…”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, the surface charge density and charge capture capacity mainly determine the output performance of triboelectric materials, [ 7–11 ] and selecting appropriate triboelectric materials is the most effective way to fundamentally improve the output performance, [ 12–17 ] so it is extremely urgent to develop triboelectric materials with high charge density. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the surface charge density and charge capture capacity mainly determine the output performance of triboelectric materials, [7][8][9][10][11] and selecting appropriate triboelectric materials is the most effective way to fundamentally improve the output performance, [12][13][14][15][16][17] so it is extremely urgent to develop triboelectric materials with high charge density. [18][19][20][21] Recently, MXene (Ti 3 C 2 T x ) has been widely used in triboelectric materials and TENG applications due to its high electronegativity, good conductivity, and high charge capture ability, which greatly improves the output performance of TENG. [22] Additionally, spherical network structure is considered as a promising structure with high specific surface area and good chemical stability.…”
mentioning
confidence: 99%